Apakah Umpan Balik dan Insentif masih Penting Bagi Karyawan non Manajemen? (Studi Laboratori Eksperimen) - Apriwandi Apriwandi (Jurnal Ilman: Jurnal Ilmu Manajemen, 2018)
this study examines whether financial incentives and feedback types have an influence on commitment and self-efficacy in improving performance through task motivation. Another thing that researchers observe is to investigate whether valid predictions use lower level employees. Participants of this experiment were 84 students of Faculty of Economics and Business Universitas Gadjah Mada. The results of this experimental study found that performance and reward feedback had no effect on the dimensions of commitment and self-efficacy in lower level employees. Performance feedback is negatively related to three dimensions of commitment and self-efficacy, while performance-based rewards are positively associated with one dimension of normative commitment. In addition, insignificant motivation relates to two of the three dimensions of commitment and self-efficacy. Significant normative commitment is positively related to the motivation of lower-level employee tasks. The implications of this study illustrate that control mechanisms do not work to increase employee commitment and self-efficacy and increase employee motivation. As well as the design of incentives and feedback can not improve employee performance